Analysis of survival factors after hepatic resection for colorectal cancer liver metastases: Does the R1 margin matter? - Ai, Xiang-nan; Tao, Ming; Wang, Hang-yan; Li, Jing-lin; Sun, Tao; Xiu, Dian-rong (Frontiers in Surgery, 2023)
Introduction: The effect of liver margin on colorectal cancer liver metastases (CRLM) after hepatectomy has been controversial. In this study, we conducted a postoperative follow-up study of 205 patients with CRLM to clarify whether a positive margin is significant and to define the risk factors affecting CRLM survival. Methods: The data of 205 patients with CRLM who underwent surgical treatment at Peking University Third Hospital in the Department of General Surgery from January 2009 to December 2020 were retrospectively analyzed. The general data, surgical data and postoperative follow-up of the patients were statistically analyzed. Results: There were 130 cases (63.4%) of R0 resection and 75 cases (36.6%) of R1 resection. There were 136 males and 69 females, age 61±11 years, and body mass index (BMI 24.5±3.3 kg/m2). The overall survival rates at 1, 3, and 5 years for the entire cohort were 93.4%, 68.4%, and 45.5% in the R0 resection group versus 93.2%, 53.7%, and 42% in the R1 resection group, respectively, which were not statistically significant (P=0.520). The 1-, 3-, and 5-year disease-free survival rates of 63.2%, 33.3%, and 29.7% were significantly better in the R0 resection group than in the R1 resection group of 47.9%, 22.7%, and 17.7% (P=0.016), respectively. After multivariable analysis, carbohydrate antigen 19-9 (CA19-9) >39 U/ml (HR=2.29, 95% CI: 1.39-3.79, P=0.001), primary tumor perineural invasion (HR=1.78, 95% CI: 1.01-3.13, P=0.047), and BMI>24 kg/m2 (HR=1.75, 95% CI: 1.05-2.93, P= 0.033) were independently associated with poorer overall patient survival. The number of liver metastases >2 (HR=1.65, 95% CI: 1.10-2.47, P=0.016), the maximum diameter of metastases ≥50 mm (HR=1.67, 95% CI: 1.06-2.64, P=0.026), and vascular invasion of the primary tumor (HR=1.65, 95% CI: 1.03-2.64, P=0.038) were also independently associated with poorer disease-free survival. Conclusion: In patients undergoing hepatectomy for CRLM, the negative effect of the R1 margin should be downplayed. Although the disease-free survival of the R1 margin is shorter than that of the R0 margin, it has no impact on overall survival. To improve overall survival, extra attention should be given to the factors of BMI, CA19-9, and the presence of perineural invasion of the primary tumor.